2014
DOI: 10.1111/rda.12386
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Perilipin 2 (PLIN2) in Porcine Oocytes During Maturation

Abstract: Perilipins have been reported to limit the interaction of lipases with neutral lipids within the droplets, thereby regulating neutral lipid accumulation and utilization. This study aimed to identify the location and expression of PLIN1 and PLIN2 in porcine oocytes during maturation. Quantitative real-time polymerase chain reaction (qRT-PCR), immunostaining and Western blot methods were used to characterize the expression and distribution patterns of PLIN1 and PLIN2 in porcine oocytes. The results showed that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…This suggests that higher FA concentrations, including saturated FAs in prepubertal FF, may have a regulatory effect on the expression of genes related solely to lipid metabolism during embryo development. Our results showed similar levels of PLIN2 expression in oocytes of P and C pigs and no change following in vitro maturation, consistent with other results in porcine and bovine oocytes 53 . Perilipins were found in various tissues, while only PLIN2 was present in oocytes of different species showing lipid droplet coating distribution.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that higher FA concentrations, including saturated FAs in prepubertal FF, may have a regulatory effect on the expression of genes related solely to lipid metabolism during embryo development. Our results showed similar levels of PLIN2 expression in oocytes of P and C pigs and no change following in vitro maturation, consistent with other results in porcine and bovine oocytes 53 . Perilipins were found in various tissues, while only PLIN2 was present in oocytes of different species showing lipid droplet coating distribution.…”
Section: Discussionsupporting
confidence: 92%
“…PLIN1, PLIN2 and PLIN3 are members of the PAT family of proteins [ 27 ], which controls the interaction between lipases and LDs; indeed, PLIN2 has been shown to be associated with lipid accumulation [ 28 ]. PLIN2 has been identified in mouse [ 29 ], porcine [ 30 ] and bovine oocytes [ 31 ] and bovine embryos [ 32 ]. In these studies, PLIN2 was shown to co-localize with LDs, indicating its role as a major LD protein in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Lep, a key factor in appetite, can inhibit feed intake 18, 19 and Lep mRNA was significantly decreased by the HS diet. Genes related to lipogenesis were significantly decreased in mice fed the HS diet, including those involved in fatty acid and lipid biosynthesis and transport (Scd2, Fabp5, Thrsp and Hmgcr) 2023 , lipid endocytosis (Ldlr) 24 , and lipid esterification (Dgat2, Mogat2 and Plin2) 2527 . Acsl6 is a negative regulator of lipid metabolism 28 .…”
Section: Discussionmentioning
confidence: 99%